2013
DOI: 10.1089/acm.2012.0177
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect Between Juzen-taiho-to, a Japanese Traditional Herbal Medicine, and Gemcitabine Single-Agent Chemotherapy for Advanced Biliary Tract Cancer

Abstract: This is the first report of the successful treatment of advanced biliary tract cancer with gemcitabine single-agent chemotherapy in combination with Juzen-taiho-to (JTT), a Japanese traditional herbal medicine. An 84-year-old woman was referred to our hospital with general fatigue and appetite loss; she was diagnosed with advanced biliary tract cancer and accompanying colonic invasion and hepatic metastasis. The patient's response to combination chemotherapy was extremely good, and her tumors disappeared. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…40 Furthermore, a study on advanced biliary tract cancer has shown that the tumor was successfully treated by combining GEM single-agent chemotherapy with JTT. 41 A marginal impact on overall survival of advanced pancreatic cancer patients was observed following treatment with JTT combined with GEP (GEM + 5-fluorouracil + cisplatin) therapy. 42 While MDSC's role was not described in these 2 studies, their observations suggest that using a combinatorial cancer immunotherapy (ie, JTT and GEM) may represent a strategy for a more effective MDSC targeting.…”
Section: Discussionmentioning
confidence: 99%
“…40 Furthermore, a study on advanced biliary tract cancer has shown that the tumor was successfully treated by combining GEM single-agent chemotherapy with JTT. 41 A marginal impact on overall survival of advanced pancreatic cancer patients was observed following treatment with JTT combined with GEP (GEM + 5-fluorouracil + cisplatin) therapy. 42 While MDSC's role was not described in these 2 studies, their observations suggest that using a combinatorial cancer immunotherapy (ie, JTT and GEM) may represent a strategy for a more effective MDSC targeting.…”
Section: Discussionmentioning
confidence: 99%
“… 35 A case report suggested that SJDBT combined with gemcitabine enhances the antitumour effects in advanced biliary tract cancer. 36 Furthermore, SJDBT protects against carbon tetrachloride-induced anorexia and hepatotoxicity, 37 protects the gastric mucosa by exerting antioxidant effects, 38 inhibits retinal neovascularisation by inhibiting angiogenesis 39 and restraint stress. 40 Its potential therapeutic effect on Alzheimer’s disease has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some studies revealed TJ-48 might play a role in immune regulation and tumor treatment (Ikemoto et al, 2014 ). This medication can alleviate side effects caused by chemotherapy and radiotherapy during the treatment of DSM, and also prevent metastasis (Nishiuchi et al, 2013 ; Amitani et al, 2015 ). Ikemoto discovered TJ-48 could increase activity of T cells, based on decreased Foxp3 + Tregs in patients with advanced pancreatic cancer (Ikemoto et al, 2014 ).…”
Section: Chinese Herbal Formulations For Dsmmentioning
confidence: 99%
“…Ikemoto discovered TJ-48 could increase activity of T cells, based on decreased Foxp3 + Tregs in patients with advanced pancreatic cancer (Ikemoto et al, 2014 ). Another study indicated that TJ-48 might slow liver cancer progression and lengthen recurrence-free survival by suppressing Kupffer cell-mediated oxidative stress (Nishiuchi et al, 2013 ).…”
Section: Chinese Herbal Formulations For Dsmmentioning
confidence: 99%